Control of attosecond light polarization in two-color bicircular fields - Jimenez-Galan, Alvaro; Zhavoronkov, N.; Ayuso, David; Morales, F.; Patchkovskii, S.; Schloz, M.; Pisanty, Emilio; Smirnova, Olga; Ivanov, Mikhail (Physical Review A, 2018)
We develop theoretically and confirm both numerically and experimentally a comprehensive analytical model which describes the propensity rules in the emission of circularly polarized high harmonics by systems driven by two-color counter-rotating fields, a fundamental and its second harmonic. We identify and confirm the three propensity rules responsible for the contrast between the 3N+1 and 3N+2 harmonic lines in the HHG spectra of noble gas atoms. We demonstrate how these rules depend on the laser parameters and how they can be used in the experiment to shape the polarization properties of the emitted attosecond pulses.
CRIS-Team Scopus Importer:2023-04-20